Iconicity as a General Property of Language: Evidence from Spoken and Signed Languages - Perniss, Pamela; Thompson, Robin; Vigliocco, Gabriella (Frontiers in Psychology, 2010)
Current views about language are dominated by the idea of arbitrary connections between linguistic form and meaning. However, if we look beyond the more familiar Indo-European languages and also include both spoken and signed language modalities, we find that motivated, iconic form-meaning mappings are, in fact, pervasive in language. In this paper, we review the different types of iconic mappings that characterize languages in both modalities, including the predominantly visually iconic mappings in signed languages. Having shown that iconic mapping are present across languages, we then proceed to review evidence showing that language users (signers and speakers) exploit iconicity in language processing and language acquisition. While not discounting the presence and importance of arbitrariness in language, we put forward the idea that iconicity need also be recognized as a general property of language, which may serve the function of reducing the gap between linguistic form and conceptual representation to allow the language system to “hook up” to motor and perceptual experience.